Evaluation of the Performance of the COVID-19 Rapid Antigen Tests in a Tertiary Level Hospital in Bangladesh - Khan, Mohammad Jahidur Rahman; Raihan, Ruksana; Akram, Arifa; Roy, Sumon; Islam, Md Shahidul; Alam, Mahjabin; Quader, Mohammad Rezaul; Khatoon, Farhana Khatoon; Suzan, Ashikuzzaman; Mim, Farzana; et al. (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
The tests providing high sensitivity and specificity are essential to identify and manage COVID-19 patients.There is a heavy demand for low-cost rapid antigen tests (RATs) for COVID-19 with a decent diagnostic value. Globally, several RATs for COVID-19 have been developed, but their clinical efficacy has not been well recognized. The purpose of the study was to evaluate the performance of RATs. We conducted this prospective observational study at Shaheed Suhrawardy Medical College hospital from February 2021 to April 2021 in Dhaka, Bangladesh. This study included the patients admitted in this hospital at the COVID-19 isolation unit or referred from the triage facility of the outdoor department of this hospital suspected as COVID-19 case. Two nasopharyngeal samples were collected simultaneously. We used one sample on the spot for the RATs and the other was sent to the adjacent Shaheed Suhrawardy Medical College COVID-19 RT-PCR laboratory for real-time reverse transcription PCR (RT-PCR). The performance of the RATs was evaluated by consuming the real-time RT-PCR results as a reference. In this investigation, SARS-CoV-2 was identified in 84 (30.7%) of the 223 patients who participated. Of these 84 patients, 9 (10.7%) were asymptomatic. The overall sensitivity and specificity of RATs were 78.6% and 99.3%, respectively. The sensitivity was 81.3% in symptomatic cases and 55.6% in asymptomatic cases. There were 18 false-negatives patients, including 3 asymptomatic cases, who had a low viral load (cycle threshold(Ct) > 30). When the Ct value was up to 24, the detection rate of RATs was 100%. The detection rate was 42.3% when the Ct was >29. When symptoms began within three days, the detection rate was 92.3%. When the start of symptoms was over 7 days, the detection rate was 33.3%. RATs for COVID-19 used in this study delivered an acceptable performance in patients with high viral load and within the first week of the onset of symptoms. This method can be a supplementary method to RT- PCR for the diagnosis of symptomatic COVID-19 patients. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):58-64